Nicotinamide (niacin) supplement increases lipid metabolism and ROS‐induced energy disruption in triple‐negative breast cancer: potential for drug repositioning as an anti‐tumor agent. Issue 9 (25th March 2022) - Jung, Minsun; Lee, Kyung‐Min; Im, Yebin; Seok, Seung Hyeok; Chung, Hyewon; Kim, Da Young; Han, Dohyun; Lee, Cheng Hyun; Hwang, Eun Hye; Park, Soo Young; Koh, Jiwon; Kim, Bohyun; et al.
Abstract : Metabolic dysregulation is an important hallmark of cancer. Nicotinamide (NAM), a water‐soluble amide form of niacin (vitamin B3), is currently available as a supplement for maintaining general physiologic functions. NAM is a crucial regulator of mitochondrial metabolism and redox reactions. In this study, we aimed to identify the mechanistic link between NAM‐induced metabolic regulation and the therapeutic efficacy of NAM in triple‐negative breast cancer (TNBC). The combined analysis using multiomics systems biology showed that NAM decreased mitochondrial membrane potential and ATP production, but increased the activities of reverse electron transport (RET), fatty acid β‐oxidation and glycerophospholipid/sphingolipid metabolic pathways in TNBC, collectively leading to an increase in the levels of reactive oxygen species (ROS). The increased ROS levels triggered apoptosis and suppressed tumour growth and metastasis of TNBC in both human organoids and xenograft mouse models. Our results showed that NAM treatment leads to cancer cell death in TNBC via mitochondrial dysfunction and activation of ROS by bifurcating metabolic pathways (RET and lipid metabolism); this provides insights into the repositioning of NAM supplement as a next‐generation anti‐metabolic agent for TNBC treatment. Abstract : Nicotinamide is a niacin (vitamin B3) supplement. Using multiomics systems biology, we showed that nicotinamide increased the activities of reverse electron transport (RET) and lipid metabolic pathways in triple‐negative breast cancer (TNBC), collectively leading to an increase in reactive oxygen species (ROS) levels. The increased ROS level suppressed tumor growth and metastasis in human organoids and xenograft mouse models.